PEMBUATAN NORMA ALAT UKUR KECERDASAN EMOSI DAN NORMA ALAT UKUR HUMOR PADA REMAJA - Erik Wijaya; Debora Basaria (Provitae: Jurnal Psikologi Pendidikan, 2017)
Humor among teenagers is one form of language. Known language is an important basis for conveying messages, intentions, or objectives as the easiest container for disseminating popular elements within the community (DeVito, 2001). Research on humor has been done by linking humor with psychological aspects, but without the norm of the measuring instrument used. Based on the research on humor with emotional intelligence done by Wijaya and Basaria (2016) using a measuring instrument of emotional intelligence of humor, showed that there is a positive and significant relationship between emotional intelligence and humor neutral. As a follow-up to the results of it, we made instrument norm of sense of humor and also norms of emotional intelligence measuring instrument. The purpose of this study is to make the norms of measuring emotional intelligence and measuring instruments of humor in adolescents, aged 11-19 years old.      Keywords: Emotional intelligence instrument, humor instrument, norm